Estructura institucional de la discapacidad en el Estado colombiano. (2013)
This article suggests the need to modify the Institutional structure of disability in Colombia; adjusting it to the new conceptual models posed by the UN Convention on the Rights of Persons with Disabilities This new institutional design; proposes the creation of the Presidential Council on Disability; the National Institute on Disability; a National Disability Rights Watch; the National Disability Fund and the Deputy Attorney´s office on disability